Review of the Iranian Pteromalinae with spiculated antennae, and description of a new species of Norbanus Walker (Hymenoptera: Chalcidoidea, Pteromalidae) - Lotfalizadeh, Hossein (Zootaxa, 2015)
Based on recently collected Pteromalidae (Hymenoptera: Chalcidoidea), 13 species were identified from genera of Pteromalinae that are characterized in part by the female clava being distinctly acuminate or apically bearing a narrow spicula. Included are two species of Callitula Spinola, three species of Homoporus Thomson, seven species of Norbanus Walker, and one species of Rhaphitelus Walker. One new species, Norbanus rasplusi n. sp., is described and six species are newly recorded from Iran: Homoporus subniger (Walker), Norbanus calabrus (Masi), N. cerasiops (Masi), N. meridionalis (Masi), N. obscurus (Masi) and N. scabriculus (Nees).